6=-3L

Simple and best practice solution for 6=-3L equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6=-3L equation:


Simplifying
6 = -3L

Solving
6 = -3L

Solving for variable 'L'.

Move all terms containing L to the left, all other terms to the right.

Add '3L' to each side of the equation.
6 + 3L = -3L + 3L

Combine like terms: -3L + 3L = 0
6 + 3L = 0

Add '-6' to each side of the equation.
6 + -6 + 3L = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 3L = 0 + -6
3L = 0 + -6

Combine like terms: 0 + -6 = -6
3L = -6

Divide each side by '3'.
L = -2

Simplifying
L = -2

See similar equations:

| 3x+6+7x+4= | | 3(p-2)=18 | | 4n-7-2=17 | | 2R=20-3R | | 80v^3+16v^2+60v+12=0 | | x-9=x+15 | | 5N=4N+1 | | 1/2(6x-8) | | 2x-11=2x-11 | | 2M+3=1 | | -3v-5=-10 | | -4c-3=1 | | 8x+2-3x-4= | | 5d+2c= | | x/8=1246 | | 13w-15w=4 | | -5E=35 | | 4x-5=2x-x | | 5(Y-10)=0 | | -9f-4+f=20+16f | | x/4-5=6 | | 20=x-20x | | (4x^3-12x)+(-2x^3+10x)= | | 2x(3-y)=14x | | 5x+10=7x-28 | | 6(-3-x)-2x=14 | | I+1=-2 | | 19-x+13=2(x+13) | | 42=8n+13m | | 5x+5y=200 | | -3(4t-3)+7t=2t-2 | | 3x+25=61+3x |

Equations solver categories